Hypercalcemia in Patients with Newly Diagnosed Tuberculosis in Abuja, Nigeria - EA Dosumu; JA Momoh (Canadian Respiratory Journal)
BACKGROUND: The prevalence of hypercalcemia has not previously been determined in newly diagnosed tuberculosis (TB) patients in Nigeria.